2014
DOI: 10.3390/su6096293
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Relationship between Rural Tourists’ Satisfaction, Revisitation and Information Preferences: A Korean Case Study

Abstract: Abstract:To encourage the sustainability of rural tourism and to achieve success in the tourist industry, an understanding of the factors by which tourists are motivated to visit rural areas is required. This study aims to measure factors affecting rural tourists' satisfaction in relation to different aspects of a destination and to increase the likelihood of revisitation and recommendation. This study also attempts to examine differences in relation to satisfaction depending on the information source preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 85 publications
(102 reference statements)
2
41
0
Order By: Relevance
“…This is probably due to the fact that as shown in Table 2, the sample respondents prefer to short-term trips (i.e., the length of stay per trip is only 3 days). In addition, according to Cho et al [26] and Rural Resource Development Institute [27], Korean rural tourists do not in general intend to stay for a long duration in the rural tourism experience. This variable, however, appears to be significant for the respondents in the other model, who have a longer travel distance and time and thus longer expected length of stay.…”
Section: Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably due to the fact that as shown in Table 2, the sample respondents prefer to short-term trips (i.e., the length of stay per trip is only 3 days). In addition, according to Cho et al [26] and Rural Resource Development Institute [27], Korean rural tourists do not in general intend to stay for a long duration in the rural tourism experience. This variable, however, appears to be significant for the respondents in the other model, who have a longer travel distance and time and thus longer expected length of stay.…”
Section: Model Resultsmentioning
confidence: 99%
“…The recruitment of potential survey respondents took place through contact by a market research survey firm, Global Research Co. We used a random sampling method to ensure each household has the same probability of being chosen [26]. The initial contact outlined the intent and purpose of the survey and then the recipient was invited to participate.…”
Section: Questionnaire Surveymentioning
confidence: 99%
“…The level of overall satisfaction with holiday experiences had the greatest impact on the intention to revisit the same destination (Cho et al, 2014). The finding of this study shows that cluster development dimensions, including the core resources and attractions, destination management, complementary conditions and demand conditions, significantly influence the intention to revisit among visitors and generate a positive impact on theme parks' operational survival.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, a study from Dayour and Adongo (2015) contended that satisfied tourists are more likely to revisit; it is for that reason vital for service providers in of any kind capacity to ensure that tourists are satisfied with the services offered to them so as to generate repeat visits; therefore, this requires destination management to be effective. Cho, Byun & Shin (2014) claimed that repeat visitors may be also influenced by these positive information sources, and that tourist destination promotion will result in other economic incentives in rural areas. Information sources and tourist destination promotion were part of the destination management's subfactors.…”
Section: The Relationship Between Visitor Experience and Intentions Tmentioning
confidence: 99%
“…In the field of tourism, satisfaction was a concept from affective component and mainstream concept tested as the antecedent of inten-tion loyalty (Kozak, 2001 Cho et al, 2014). Although the majority of empirical findings showed that satisfaction had significant direct impact on intention loyalty, the study of Bigne et al (2001) towards the visitors of two tourism destinations in Valencia, Spain, namely Peniscola and Torrevieja with two concepts to represent conative loyalty, namely intention to revisit and intention to recommend instead found that satisfaction had positive and significant impact on intention to recommend on both samples, but the indicator of intention to revisit showed a different result.…”
Section: Introductionmentioning
confidence: 99%